An Analysis on Latest Economic Policy and the Social Development: Features and Impacts: Revisiting and redefining the vision for social issues in the global sustainable development framework (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The present substances exhibit the proceeded with significance of this establishing vision—the requirement for research on social issues that is free, coordinated to policy making, and receptive to changes in the worldwide setting. Value, rights and social equity—issues that put people at the core of the development procedure—have returned as the essential standards of another worldwide supportable development structure. In any case, the present substances likewise advise us that such a plan must be constantly returned to and renegotiated, needs reclassified and bolstered with new proof.